The Urgency of Imposing Sanctions on Schools that Neglect Child Victims of Bullying - Muhammad Rafi Risnawan; Hanifah Febriani (Proceeding International Conference Restructuring and Transforming Law, 2024)
This article reviews the urgency of imposing sanctions on schools that ignore child victims of bullying. This departs from the unrest over the rampant cases of bullying in the school environment that occur in Indonesia even at every level of education. Children who are vulnerable human beings should get legal protection for their rights that must be fulfilled as part of the subject of law. This research is normative juridical research that adopts a statutory approach. The data sources of this research are obtained from primary, secondary, and tertiary legal materials which all have relevance to the issues being studied. The objectives of this research are: 1) Knowing the sanctions received by schools that neglect child victims of bullying; and 2) Knowing the urgency of sanctions for schools that neglect child victims of bullying. The results show that there are still many cases of bullying that occur against the background of many factors. Based on the research results, it can be concluded that there are some cases where the school has firmly addressed bullying cases, but this is still not enough to represent the many other cases that have not been resolved. Schools that ignore child victims of bullying can be subject to administrative sanctions in the form of reprimands and suspensions. In addition, according to Article 76c of Law No. 35/2014, schools can be subject to criminal sanctions in the form of imprisonment and fines. The provision of sanctions against schools that commit negligence is important considering that currently there are no strict sanctions for schools that neglect victims of bullying. For this reason, sanctions are needed for schools so that in future cases the school will better protect victims of bullying.